Exploration on English Listening Comprehension Motivation of Phase-B EFL Students - Vega Putri Varisah; Nurul Yaqin (Majapahit Journal of English Studies, 2025)
Listening is one of the problems in English language teaching that is often faced by teachers. Lack of practice and exercise such as listening comprehension are rarely used in the class. Researchers want to know students' motivation to learn listening. This study aims to analyze students' listening comprehension motivation in EFL students which includes three aspects: attitude, concept, and learning situation. This study used a quantitative approach and ELCMS (English Listening Comprehension Motivation Students) questionnaire to 33 students in secondary school MTs Negeri 4 Sidoarjo. The results show that one of the three indicators above that has a significant influence is the concept indicator. This is based on SEM analysis carried out via the Smart-PLS 4.0 application.